Green Growth Opportunities for Bhutan - World Bank (Washington, DC, 2014)
Bhutan has recently made significant progress in sustaining economic growth and reducing poverty. In 2012, average per capita household income was somewhat under USD 2,400/year (Living Standards Measurement Surveys 2012). Growth has averaged around 9 percent per annum over the past decade and is expected to be on the order of 8 percent per annum over the next five years. According to the 2012 Bhutan Poverty Analysis, 12 percent of the population are what is known as consumption poor , half the number as compared to 2007. Furthermore, extreme poverty defined as less than $1.25/day in PPP terms has fallen to only 2 percent of the total population. Bhutan has virtually eliminated extreme poverty within the living memory of one generation. Bhutan s population remains rural to a significant extent. According to a 2005 population census, 69 percent of the population lived in rural areas. And there remain significant income differences between urban and rural areas; average per capita household income in rural areas is estimated to be 28,000 Nu against 80,000 Nu in urban areas. There is, though, significant ongoing migration to population centers in search of increased opportunities. The 2005 urban population share of 31 percent of total population represents a substantial increase from only 5 percent in 1995.